Pengaruh Pendapatan dan Pengetahuan Pegawai Terhadap Pembayaran Zakat Profesi di Kantor Inspektorat Kabupaten Deli Serdang - Muslim, Rany; Marliyah, Marliyah; Inayah, Nurul (LPPM Universitas Labuhanbatu, 2023)
This study aims to determine how the influence of income and knowledge of employees on the payment of zakat profession.This type of research uses quantitative research methods. Data collection was carried out by distributing questionnaires using a likert scale to muslim employees at the Inspectorate Office of Deli Serdang regency. The sampling technique used is to use total sampling, where the number of populations and samples are the same. So that the number of respondents used is 55 muslim employees in the Inspectorate Office of Deli Serdang regency. The data obtained will be processed using SPSS Statistic 15. Analysis includes validity test, reliability test, classical assumption test and hypothesis test. From the results of this study it is explained that the T-Test t-Table value is 2.006 and t-count is X1 = ,627, X2 = 6.012. Thus, variables X1 and X2 have a significant effect on the payment of professional zakat. The results of the F test explain that in the F test obtained F table value of 3.17 and F count of 54.399 and significance level of 0.00 < 0.05 it can be concluded that X1 and X2 simultaneously have a significant effect. effect on the variable payment of professional Zakat at the Inspectorate Office of Deli Serdang regency. Coefficient of determination obtained correlation value of R is 0.823. And the value of the coefficient R square of 0.677 or 67.7% which means the ability of the independent variable in explaining the dependent variable of 67.7%, the remaining 33.3% is explained by other variables that are not discussed in this study.